Application of time-aware retransmission against reflection signal interferences in Internet of things - Han LUO; Yuhong LIU; Hongguang ZHANG; Chong ZHANG; Yuan’an LIU (物联网学报, 2019)
In the enclosed spaces,wireless transmissions lead to the strong interferences of reflection signals,because of multipath effects.However,how to reduce the reflection signal effect on wireless transmissions is a kernel problem to expand the application scope of Internet of things.The time-aware retransmission MAC (TR-MAC) was proposed,which can adjust the time delay of each frame and reduce the interference caused by the reflected signal by using the reflection loss of the space conductor surface.In order to prove the adaptability of TR-MAC,an experimental environment that can generate strong reflection interference signals was used.The experimental results proved the feasibility and effectiveness of the TR-MAC in different environments.In a sense,TR-MAC extends the application of wireless communication in strongly reflective space.Besides,in the application of the Internet of things in the aircraft,ship and satellite,TR-MAC can realize wireless transmission instead of part of the wired transmission,so as to improve the system reliability,effective weight reduction and other important goals.